I-PreFer Study: A Discrete Choice Experiment to Explore Patient, Caregiver and Pulmonologist Preferences of Idiopathic Pulmonary Fibrosis Pharmacological Treatment Options - Hollmen M; Wijsenbeek M; Bromilow T; Smith AB; Mealing S; Lewis D; Galvin L; Jones S; Asijee G; Soulard S; Froidure A (Patient Preference and Adherence, 2023)
Maria Hollmen,1 Marlies Wijsenbeek,2 Tom Bromilow,3 Adam B Smith,3 Stuart Mealing,3 Damian Lewis,3 Liam Galvin,4 Steve Jones,4 Guus Asijee,5 Stéphane Soulard,5 Antoine Froidure6,7 1Faculty of Medicine, University of Helsinki, Helsinki, Finland; 2Centre of Excellence for Interstitial Lung Diseases and Sarcoidosis, Department of Respiratory Medicine, Erasmus MC, University Medical Center, Rotterdam, the Netherlands; 3York Health Economics Consortium (YHEC), York, UK; 4European Pulmonary Fibrosis & Related Disorders Federation, Overijse, Belgium; 5Boehringer Ingelheim, Amsterdam, the Netherlands; 6Service de Pneumologie, Cliniques Universitaires Saint-Luc, Brussels, Belgium; 7Institut de Recherche Expérimentale et Clinique, UCLouvain, BelgiumCorrespondence: Maria Hollmen, Faculty of Medicine, University of Helsinki, Haartmaninkatu 8 P.O. Box 63, Helsinki, 00014, Uusimaa, Finland, Email maria.hollmen@hus.fiPurpose: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, and ultimately fatal lung disease that, while rare, has seen incidence rise over time. There is no cure for IPF other than a lung transplant, though two antifibrotic (AF) drugs do exist to slow disease progression. While these drugs are efficacious, they are both associated with differing profiles of adverse events. This study aimed to elicit patient, caregiver and pulmonologist preferences on the treatment profiles of AFs via a discrete choice experiment (DCE).Patients and Methods: The DCE and associated survey were distributed across 7 European countries, and bespoke DCEs were developed for patients/caregivers and pulmonologists. After collaboration with European Pulmonary Fibrosis & Related Disorders Federation (EU-PFF) and expert pulmonologists, respectively, a patient/caregiver DCE with 5 attributes and a pulmonologist DCE with 6 attributes were finalized. The DCEs had a blocked approach to reduce participant burden and were distributed on an online survey platform. Preferences were estimated through conditional multinomial logit regression analysis.Results: Ninety-five patients, 22 caregivers and 115 pulmonologists fully completed their respective DCEs. Overall, patients and caregivers preferred management of treatment-related adverse events over both survival benefits and disease progression. Nearly all preference levels were found to be significantly different from their reference level. In contrast, pulmonologists showed a greater preference for control of lung function and exacerbations over adverse events. Although there were relative differences between the univariate subgroups in terms of the preference weights, most of these were not statistically significant.Conclusion: The outcomes from this study suggest that while patients and caregivers had similar preferences for characteristics of IPF treatments, pulmonologists did not share those same preferences. Patients and caregivers preferred safety, while pulmonologists preferred efficacy. These differences should be considered by clinicians to better involve the patient in treatment decision-making for IPF.Keywords: treatment preferences, online survey, outcomes research, lung disease